Echocardiographic Assessment of Left Ventricular Systolic Function in Lymphoma Patient After Initial Dose of Chemotherapy in Baghdad Teaching Hospital - Dr. Firas Yahya Ibrahim; Prof. Hasan Farhan; Prof. Ali Mohameed Jawad (Zien Journals, 2024)
Despite cancer therapeutics-related cardiac dysfunction (CTRCD) can be initially asymptomatic, if not detected and properly managed, it may progress to severe and irreversible heart failure. Therefore, identification of high-risk patients and early detection of subclinical myocardial dysfunction are fundamental tasks for the management of cancer patients undergoing chemotherapy, involving both cardiologists and oncologists. LVEF has low sensitivity for the detection of small changes in LV function. LVEF calculated by conventional 2DE often fails to detect small changes in LV contractility because of several factors. These factors include LV geometric assumptions, inadequate visualization of the true LV apex, lack of consideration of subtle regional wall motion abnormalities, and inherent variability of the measurement. Accordingly, strategies using newer echocardiographic technology, such as STE-derived strain imaging for the early detection of subclinical LV systolic dysfunction. GLS being the most robust and reproducible among the myocardial strain parameters, this parameter has raised the interest of the investigators to detect early and subclinical myocardial dysfunction in patients at risk of CTCRD
Keywords: detected; patients; parameters; subclinical